PENINGKATAN HASIL BELAJAR SISWA PADA ELEMEN BHINNEKA TUNGGAL IKA MENGGUNAKAN MODEL DISCOVERY LEARNING DI KELAS IV SDN 05 TAROK DIPO KOTA BUKITTINGGI - Atsilah Syahni, Alya; Anita, Yesi; Bungsu Ladiva, Hasmai; Tri Wulandari, Fikhen (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the improvement of student learning outcomes on the Bhinneka Tunggal Ika element of Pancasila Education through the implementation of the Discovery Learning model in the fourth grade of SDN 05 Tarok Dipo, Bukittinggi City. Preliminary observation showed that only 42.86% of students reached the minimum learning target (KKTP) of 70, indicating that learning outcomes were still low due to teacher-centered instruction and an unsystematic deep-learning lesson plan (RPM). This research was a classroom action research conducted in two cycles, each consisting of planning, acting, observing, and reflecting stages. The subjects were 28 fourth-grade students. Data were collected through assessment sheets, observation sheets, tests, and documentation, and were analyzed using quantitative and qualitative techniques. The results showed consistent improvement in all observed aspects. The quality of the RPM increased from 87.5% in Cycle I to 100% in Cycle II. Teacher activity increased from 81.25% to 96.87%, and student activity increased from 84.37% to 96.87%. Student learning outcomes also improved significantly: the attitude aspect rose from 73.78 to 88.05, the knowledge aspect from 67.5 to 91.42, and the skill aspect from 74.53 to 92.16. By the end of Cycle II, all 28 students (100%) had reached the KKTP. These findings indicate that the Discovery Learning model, supported by interactive digital media, effectively improves the planning, implementation, and learning outcomes of Pancasila Education in elementary school.